La economía social y solidaria. Un modelo empresarial del futuro - Albarán Camuendo, Juan Carlos (2013)
Our society has been ruled by the economy from the beginning of the world, the main purpose of the society of all times is to bring whole welfare to the needs of people being part of the government or a society; and also offering good life to the individuals in a competitive society. By looking after all these needs, for the welfare of the Ecuadorians and that all this considered population get the benefits on the Official Bulletin State Journal Nº 444, where the law is published. The Law popular and solidarity economy and Popular Financial Sector and Solidarity; the National Assembly based its publication on Article 283 of the Constitution of the Ecuadorian Republic.